Channelizing the Therapeutic Powers of Sufi Poetry in the Modern World - Hussain, Riaz; Rahman, Syed Hammad ur; Asif, Muhammad; Ghani, Mamuna (Richtmann Publishing, 2012)
In the post-9/11 scenario, modern world appears to be rife with wars, suspicion, threats, mistrust, insecurity, arson andinflation. What seems to loom large is the global fear of a third world war. The world searches for channels which can ensure lastingpeace and minimize violence in the world. In order to achieve harmony and peace in the world, in addition to other things, promotingliterature that preaches universal love may help. We need to channelize therapeutic words from literature that can purge our mind-sets ofjingoistic, chauvinistic and xenophobic tendencies and ethno-linguistic conflicts. The therapeutic power of words is channelized inPsychotherapy, bibliotherapy and poetry therapy. Bibliotherapy and poetry therapy have been applied in various rehabilitation centersand hospitals to cure people of their memories of their traumatic experiences. News reports reveal that the poetry of Rumi has risen fromthe Mediterranean region and entered American culture. Generalizing from such developments, experiments, reports and observations,the paper explores the possibility of large scale, mass poetry therapy involving multicultural and multilingual people of the global village.It tries to figure out poetry that can bridge gaps in the global community. It looks at the capacity and suitability of the classical MuslimSufi poetry to meet these needs and challenges of the present age of information. Being an embodiment of universal love, peace andhumanitarianism, if promoted effectively on media, it may help in minimizing war and violence in the world.